New Energy Vehicle Battery SOC Evaluation Method based on Robust Extended Kalman Filterd. Issue 1 (1st February 2022) - Zhang, Jian; Wang, Qiang; Meng, Fanjie; Shi, Hang; Xi, Yanjun
Abstract: In actual charging/discharging scenarios of new energy vehicles, low temperature, natural disasters, extreme weather, electromagnetic radiation and other factors will cause strong noise interference in SOC evaluation. Aiming at the problem of SOC evaluation accuracy in extreme environments, a power battery SOC evaluation method based on robust Kalman filter is proposed. The experimental results prove that the method is suitable for the accurate assessment of SOC in the charging/discharging process of the power battery of new energy vehicles under the interference of complex and harsh environment noise, and it has good robustness.